Intratextualidad en el poema "Los heraldos negros" de César Vallejo, versión primera-versión oficial, e intertextualidad con El grito de Edvard Munch - Campos López, Ronald (2012)
The aim is to analyze intratextual relations between the first version and the official version of the poem “The Black Heralds” by Cesar Vallejo, based on the phonetic, semic and syntagmatic graphics of the Baroque text according to Severo Sarduy; in addition, the intertextual relations of both texts are compared to “The Scream” by Edvard Munch, as reminiscent of a textuality of existential perspective.